(untitled) - Huxley, Julian (New York, 1954)
The Middle East gives a unique picture of the growth of civilization, from its earliest origins up to the present. Ur and Babylon, Nineveh and Persepolis, Isfahan and Shiraz, Baghdad and Ctesiphon, Petra and Palmyra, Baalbek and Byblos, Damascus and Aleppo, Sidori and Tripoli, Jerash and Dura, Ras Shamra and Qalat Seman, fortresses and castles of every period - what a list! And then there is Egypt and Turkey, which are also included in this book. Huxley experienced the overpowering physical spectacle of the Bekaa Valley; discussed education and the place of women with King Abdullah; he visited the gigantic ruins of ancient tombs and temples, and the conglomeration of gods and goddesses - Baal, Osiris. Ashtaroth, Moloch and hundreds more whose worship was founded on slavery and sacrifice and is now forgotten as the dust. Under his pen, the Middle East is populated again with the flourishing empires of four thousand years, dark, bizarre and hostile, rich both in splendour and horror.
Keywords: Trung Đông,Middle East; Mô tả và du hành,Description and travel